(untitled) - Kittirath, Pisavanh (Cần Thơ, 2019)
The objective of this study was to investigate the street food consumption by consumers (n=410) to get insight into two popular street foods are Vietnamese sandwiches (34.63%) and sugarcane juice (24.51%) were consumed popularly and possibly high risk of food safety by means of surveys.
Keywords: Food safety issues,Vấn đề an toàn thực phẩm